Neuronal function is necessary but not sufficient for consciousness: consciousness is necessary for will - Nussbaum, David; Ibrahim, Khadija (Frontiers in Integrative Neuroscience, 2012)
Behavioural neuroscience has presented philosophers with the task of clarifying the relationship between neural determinism and free will. If neural functions encode information and govern decision-making, are the constructs of will, agency and indeed morality illusions of pre-scientific ignorance? This article will argue that neuronal function is necessary for representing distinct sensory-perceptual, cognitive, motivational, emotional states and motor functions. However, neural transmission and action potentials are simply chemical-physical representations of these informational states but are not the embodiment of consciousness itself. By some yet undiscovered mechanism, consciousness “reads” the neuronal events into conscious experience. Absent a particular specialized brain region or sufficient relevant transmitters and receptors, relevant information cannot be processed and the individual cannot be conscious of that informational state. In natural and many artificial communication systems, communications proceed bi-directionally. By an argument of symmetry, if neuronal activity can communicate with consciousness, there is no reason to preclude consciousness from communicating back and influencing neuronal function. In the intervening conscious moment, information from diverse perceptual, motivational, cognitive and emotional sources is weighted and resultant will results. This process then biases resultant neural processes to actualize the willed target. This approach is limited in terms of operationalization into an experimental study because at present, there is no method to measure consciousness independent of neuronal function and subjective report.